2022
DOI: 10.1177/03080226221092689
|View full text |Cite
|
Sign up to set email alerts
|

Exploring potential for occupational therapy practice models within areas of social deprivation: A qualitative inquiry within a community-centred food cooperative

Abstract: Background A health inequalities gap exists between wealthy and deprived areas. Community-level occupation-focused interventions may support citizens and address inequities within their environments. Since the global financial crash of 2008 and fiscal policy changes within the United Kingdom, there has been a rise in food insecurity. Community volunteer initiatives have responded by providing for their residents. The aim of this study was to explore how occupational therapists may be agents for social change t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…By changing the institutions, strategies, and narratives of local development, the transformation of a transactional food bank organisation/provision to a food co-operative may become possible. Indeed, co-ordinators from the food co-operative studied by Adams et al (2022) provided external guidance to the study presented here, allowing for lesson learning. Other examples of alternative forms of provision exist in Northumberland, for example, Northern Soul Kitchen in Berwick has a 'pay-as-you feel' approach and makes use of unsold food (however, tellingly, this social enterprise faces funding pressures (Northumberland Gazette, 2023)).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By changing the institutions, strategies, and narratives of local development, the transformation of a transactional food bank organisation/provision to a food co-operative may become possible. Indeed, co-ordinators from the food co-operative studied by Adams et al (2022) provided external guidance to the study presented here, allowing for lesson learning. Other examples of alternative forms of provision exist in Northumberland, for example, Northern Soul Kitchen in Berwick has a 'pay-as-you feel' approach and makes use of unsold food (however, tellingly, this social enterprise faces funding pressures (Northumberland Gazette, 2023)).…”
Section: Discussionmentioning
confidence: 99%
“…One outcome of this programme is the development of supply teacher’s co-operative to address insecure work, falling incomes and extractive business models (CLES, 2022). In Preston, where the City Council is one of the pioneers of CWB in England, a food subscription co-operative has been initiated to ground the issue of food poverty within a broader institution and set of practices, comprising democratic membership, affordable food and fostering experience in co-operative organisation (Rawlinson and Khan, 2021, see also Adams et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a participant's choice of food pantry, motivational interviewing, and individualized service referrals resulted in improvements in participants' food security and self-sufficiency scores (Martin et al 2013). Adams et al (2022) concluded that OTPs need to work with communities when seeking to address social issues, which include food insecurity. Schmelzer and Leto (2018) used an occupation-based program consisting of a group discussion of goals, an experiential activity, and group reflection, resulting in statistically and clinically significant improvements in perceived satisfaction and performance of food-related activities.…”
Section: Discussionmentioning
confidence: 99%